High Frequency In vitro Propagation of Polianthes tuberosa (Biological Sciences - PJSIR, 2006)
Calli induced on MS medium supplemented with 10 mM a-naphthaleneacetic acid (NAA) grew extensively when cultured on MS medium modified with 4 mM 2,4-dichlorophenoxyacetic acid (2,4-D), producing on an average four shoots per callus culture. The addition of 1 mM L-arginine in the culture media enhanced the induction rate upto 10 shoots per callus culture in 12 weeks. When 2-3 cm long regenerated shoots were replanted on MS medium with 20mM 6-benzylyadenine (BA) and 4 ?M 2,4-D, shoots the proliferated at the cut ends. Floral axis buds produced 3-4 cm long multiple shoots on NAA and BA. New shoots regenerated from the calli produced at the base of shoots subcul- tured on 10 mM NAA. Repetition of shoot development, callus formation, and again shoot formation on 10 mM NAA and 2 mM BA greatly increased the number of plants from single shoots. Eighty five percent bulb explants produced 290 shoots in 12 weeks directly on 15 mM BA and 5 mM NAA. The somatic psuedoembryos formed in the calli were dormant.